On the joint distribution of wave heights and periods: the role of the spectral bandwidth - Rodriguez, G. R.; Rubio Royo, Francisco; Pacheco Martínez, Mercedes; Martínez Marrero, Antonio (Journal of Offshore Mechanics and Arctic Engineering, 1999)
The influence of the spectral bandwidth on the probabilistic structure of the joint distribution of wave heights and periods is analyzed by means of simulated wave records. In particular, the effects of the spectral bandwidth on the asymmetric and bimodal structure of the distributions are examined. Moreover, the adequacy of some theoretical models to describe such features is considered.